Effectiveness of the "Sayang Warga" Application as a Potential Solution for Stunting Reduction in Surabaya - Tri Prayoga, Nugraha (Journal of Governance and Administrative Reform, 2024)
Abstract This study aims to explain the effectiveness of the Sayang Warga service application in accelerating the reduction of stunting in the government of Surabaya City, using the service effectiveness system theory proposed by Delone and Lean. Stunting is a condition of chronic malnutrition that occurs in children under five years old. This research employs a qualitative research method and is conducted in Surabaya City. The study utilizes secondary data from literature sources and applies an interactive model of qualitative data analysis techniques. The results of this study indicate the effectiveness of the Sayang Warga application in addressing stunting in Surabaya City. The application serves as an innovative breakthrough, facilitating the Surabaya City Government in stunting data collection. Consequently, with this application, the Surabaya City Government is more organized in preventing stunting. Keywords: effectiveness; application; public service innovation; stunting   Abstrak  Tujuan penelitian ini yaitu menjelaskan tingkat efektifitas aplikasi layanan sayang warga dalam mempercepat penurunan stunting pada pemerintah Kota Surabaya dengan menggunakan teori efektivitas system layanan yang dikemukakan oleh Delone and Lean. Stunting adalah kondisi kekurangan gizi kronis yang terjadi pada anak dibawah usia lima tahun. Penelitian ini menggunakan metode penelitian kualitatif. lokasi di Kota Surabaya. Penelitian ini menggunakan data sekunder dari pustaka. Penelitian ini menggunakan teknik analisis data kualitatif model interaktif. Hasil dari penelitian ini menunjukkan tingkat keefektivan aplikasi Sayang Warga terhadap pengentasan stunting di Kota Surabaya, karena aplikasi tersebut menjadi terobosan baru untuk dapat dimanfaatkan serta memudahkan Pemerintah Kota Surabaya dalam melakukan pendataan stunting. Berkat adanya aplikasi ini pemerintah Kota Surabaya lebih terorganisir dalam mencegah stunting. Kata kunci: efektivitas; aplikasi; inovasi pelayanan publik; stunting.